Analisis Pengelolaan Aset Tetap Daerah Pada Badan Pengelola Keuangan Dan Aset Daerah (BPKAD) Provinsi Sumatera Selatan - Rita Agustina; Jusmani Jusmani; Reva Maria Valianti (Jurnal Media Akuntansi (Mediasi), 2022)
ABSTRACT This study expects to examine the administration of local fixed resources, particularly fixed resources of structures and structures inside the extent of the utilization of Regional Property (BMD) through a rent component at the Regional Financial and Asset Management Agency (BPKAD) of South Sumatra Province. The number of inhabitants in this examination is the administration of endlessly fabricating resources that have been completed at the Regional Financial and Asset Management Agency (BPKAD) of South Sumatra Province. This examination technique utilizes spellbinding subjective where the investigation interaction is by gathering and breaking down the administration of territorial fixed resources. The information utilized are information on objects of land and structures that are worked together as leases at the Regional Financial and Asset Management Agency (BPKAD) of South Sumatra Province. The consequences of this study presume that the administration of provincial fixed resources, particularly fixed resources of structures and structures inside the extent of the utilization of Regional Property (BMD) through a rent component at the Financial and Blood Asset Management Agency (BPKAD) of South Sumatra Province is as per the Regulation of the Minister of Home Affairs Number 19 2016 concerning Guidelines for the Management of Regional Property and the use of territorial property rental exercises have been running ideally.   Keywords : Regional Fixed Asset Managemen, Regional Property (BMD), Utilization of BMD in the form of rentals, Buildings and Buildings.  ABSTRAK Kajian ini berencana memecah administrasi sumber daya tetap provinsi, khususnya sumber daya tetap struktur dan struktur dalam lingkup pemanfaatan Barang Milik Daerah (BMD) melalui instrumen sewa di Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Sumatera Selatan. Provinsi. Jumlah penduduk dalam eksplorasi ini merupakan administrasi sumber daya fabrikasi tanpa henti yang telah diselesaikan di Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Provinsi Sumatera Selatan. Strategi pemeriksaan ini menggunakan subyektif yang jelas dimana interaksi investigasinya adalah dengan mengumpulkan dan membedah administrasi sumber daya tetap lokal. Informasi yang digunakan adalah informasi mengenai obyek tanah dan bangunan yang dikerjasamakan sebagai sewa di Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Provinsi Sumatera Selatan. Konsekuensi dari penelitian ini adalah bahwa penyelenggaraan sumber daya tetap daerah, khususnya sumber daya tetap struktur dan struktur dalam lingkup pemanfaatan Barang Milik Daerah (BMD) melalui komponen sewa pada Badan Pengelola Aset Keuangan dan Darah (BPKAD) Selatan Provinsi Sumatera sesuai dengan Peraturan Menteri Dalam Negeri Nomor 19 Tahun 2016 tentang Pedoman Pengelolaan Barang Milik Daerah dan pelaksanaan pemanfaatan barang milik daerah sudah berjalan secara ideal. Kata Kunci : Pengelolaan Aset Tetap Daerah, Barang Milik Daerah (BMD), Pemanfaatan BMD Dalam Bentuk Sewa, Gedung dan Bangunan.